1999
DOI: 10.1016/s0378-1097(98)00574-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-co-regulated pilus cluster in non-O1, non-toxigenic Vibrio cholerae: evidence of a third allele of pilin gene

Abstract: Polymerase chain reaction has been used to detect the presence of the virulence associated gene, tcpA and part of the promoter distal region of the toxin-co-regulated pilus cluster in non-O1, non-toxigenic, Vibrio cholerae. The amplified regions were characterised by restriction fragment length polymorphism and heteroduplex motility assay. We describe the nucleotide sequence of the tcpA gene fragment from non-toxigenic vibrios from clinical and environmental sources. The present study shows that there are at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 17 publications
(21 reference statements)
3
32
0
Order By: Relevance
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 93%
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, two strains ± i.e., strain 151 (O34) and strain 208 (O27) isolated in Mexico and in Thailand in 1986 and 1992, respectively ± appear to be similar to these strains in that, although CT negative they were both tcpA and toxT positive [26]. Apart from the presence of a`free' RS1 element, strain AS480 was devoid of all known virulence genes associated with toxigenic V. cholerae.…”
Section: Discussionmentioning
confidence: 96%
“…In a survey that was performed for the presence of virulence associated genes in non-O1, non-O139 V. cholerae strains, they found tcpA and the putative tcp gene cluster in two distinct non-toxigenic, non-O1/non-O139 strains. As this was an unexpected result, further investigation was carried out on these two isolates (Novais et al, 1999). in the study that was performed by Singh on Territorial waters of the Baltic Sea as a source of infections caused by V. cholera non-O1, non-O139, all isolates gave negative agglutination reactions with O1 and O139 antisera.…”
Section: Discussionmentioning
confidence: 99%